The Multiple Dispositifs of (Early) Cinema - Kessler, Frank (Cinémas)

(untitled) (Cinémas, 2018)
In recent debates regarding the effects of digitalization on cinema, the concept of dispositif is generally used to refer to a model of spectatorship that was defined in the 1970s by Jean-Louis Baudry. Consequently, when theorists affirm that there is an “explosion” of the cinematic dispositif in the twenty-first century, they partake in this monolithic conception, which does not acknowledge the fact that watching films in the twentieth century occurred in a variety of ways, both diachronically and synchronically. Critiquing such a view, this article proposes to understand the concept of dispositif from the perspective of a historical pragmatics and to use it as a heuristic tool to analyze the vast range of moving image dispositifs that have existed historically, as well as the new dispositifs that emerge in today’s digital mediascape.